2022
DOI: 10.3390/cells11244125
|View full text |Cite
|
Sign up to set email alerts
|

QTLs Related to Rice Callus Regeneration Ability: Localization and Effect Verification of qPRR3

Abstract: Mature and efficient tissue culture systems are already available for most japonica rice varieties (Oryza sativa ssp. geng). However, it remains challenging to regenerate the majority of indica rice varieties (Oryza sativa ssp. xian). In this study, quantitative trait loci (QTLs) associated with rice callus regeneration ability were identified based on the plant regeneration rate (PRR) and total green plant rate (TGPR) of the 93-11 × Nip recombinant inbred line population. Significant positive correlations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Previous studies have consistently shown that cultivated rice displays a greater capacity for anther culture when compared to wild rice [11]. Furthermore, within cultivated rice varieties, japonica rice has been found to exhibit significantly higher efficiency in anther culture compared to indica rice [12][13][14][15].…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have consistently shown that cultivated rice displays a greater capacity for anther culture when compared to wild rice [11]. Furthermore, within cultivated rice varieties, japonica rice has been found to exhibit significantly higher efficiency in anther culture compared to indica rice [12][13][14][15].…”
Section: Introductionmentioning
confidence: 95%
“…The transformation frequency has a great relationship with the plant genotypes. For example, the comparison of six rice varieties (Oryza sativa L.), one of the species with the highest transformation rate, showed that different genotypes have different transformation efficiency to Agrobacterium tumefaciens [23]. Moreover, even in plants with relatively high transformation frequency (such as tobacco, potato, Arabidopsis, etc.…”
Section: Virus-induced Genome Editingmentioning
confidence: 99%
“…In recent years, a series of genes that play roles in somatic embryogenesis (SE) have been cloned and studied. Previous studies reported that the overexpression (OE) of several classic genes, including WUSCHEL ( WUS ; Lopes et al ., 2021; Wang et al ., 2022; Lu et al ., 2023; Ogura et al ., 2023), BABY BOOM ( BBM ; Li et al ., 2022; N. Wang et al ., 2023), WRKY (Zhang et al ., 2024) and LEAFY COTYLEDON1 ( LEC1 ; Wang et al ., 2009), is able to cause vegetative‐to‐embryonic transition or plant regeneration (J. Wu et al ., 2022; Yu et al ., 2023). In addition, recent advances have updated SE‐related genes, including GhRCD1 (Yuan et al ., 2023), GROWTH‐REGULATING FACTORs (GRFs; Feng et al ., 2021; Luo & Palmgren, 2021), SCARECROW‐LIKE genes CsSCL2 and CsSCL3 ( CsSCL2/3 ; Feng et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%